A 'dry eye' for victims of violence: effects of playing a violent video game on pupillary dilation to victims and on aggressive behavior - Arriaga, P.; Adrião, J. G.; Madeira. F.; Cavaleiro, I.; Silva, A. M.; Barahona, I.; Esteves, F. (Psychology of Violence, 2015)
Objective: The present experiment analyzed the effects of playing a violent video game on player's sensitivity to victimized people by measuring the involuntary pupil dilation responses (PDRs) during a passive picture viewing paradigm and examining the mediating role of PDR on aggression. Method: Participants (N = 135) were randomly assigned to play a violent video game or a nonviolent video game. The participants' PDRs were then recorded while they were exposed to pictures of alleged victims of violence displayed in negative, neutral, and positive contexts. A competitive reaction time task was also used to measure aggression. Results: Participants in the violent game condition demonstrated both a lower PDR to the victims of violence in a negative circumstances and greater aggression than participants in the nonviolent game condition. Lower PDR to victims displayed in negative context mediated the relationship between violent game play and aggression. Conclusion: The negative effects of playing violent games are a societal concern. Our results indicate that a single violent gaming session can reduce the player's involuntary PDRs to pictures of victimized people in negative context and increase participant aggression, a new relevant finding that should encourage further research in this area.